The prevalence of non-accidental trauma among children with polytrauma: A nationwide level-I trauma centre study. (August 2022) - Loos, Marie-Louise H.J.; van Rijn, Rick R.; Krug, Egbert; Bloemers, Frank W.; Ten Bosch, Jan A.; Bossuyt, P.M.M.; Edwards, Michael J.R.; Greeven, Alexander P.A.; Hulscher, Jan B.F.; Keyzer-Dekker, Claudia M.G.; de Ridder, Victor A.; Spanjersberg, W. Richard; et al.
Abstract: Objective: We aimed to investigate the prevalence and characteristics of non-accidental trauma (NAT) in children with polytrauma treated at level-I trauma centres (TC). Summary of background: Data 6–10% Of children who present at the emergency department with injuries, sustain polytrauma. Polytrauma may result from either accidental (AT) or NAT, i.e. inflicted or neglect. The prevalence of NAT among children with polytrauma is currently unclear. Methods: This is a retrospective study that included children (0–18 years) with an Injury Severity Score >15, who presented at one of the 11 Level-I trauma centers (TC) in the Netherlands between January 1, 2010 and January 1, 2016. Outcomes were classified based on the conclusions of the Child Abuse and Neglect-team. Cases in which conclusions were unavailable and there was no clear accidental cause of injuries were reviewed by an expert panel. Results: The study included 1623 children, 1452 (89%) were classified as AT, 171 (11%) as NAT; 39 (2, 4%) inflicted and 132 (8, 1%) neglect. Of pre-school aged children (<5 years) 41% sustained NAT (OR26.73, 95%CI 17.70–40.35), 35/342 (10%) inflicted and 104/342 (31%) neglect. Admission due to 'cardiopulmonary arrest' was the result of inflicted trauma (30% vs 0%, p < 0.001). NAT had a higher mortality rate (16% vs 10%, p = 0.006). Indicators of NAT were: (near-)drowning (OR10.74, 95%CI 5.94–19.41), burn (OR8.62, 95%CI 4.08–18.19) and fall from height (OR2.18, 95%CI 1.56–3.02). Conclusions: NAT was the cause of polytrauma in 11% of children in our nationwide level-I TC study; 41% of these polytrauma were the result of NAT experienced by preschool-aged children. Our data show the importance of awareness for NAT. Highlights: The nationwide level-I trauma study presents the prevalence of non-accidental trauma in children with polytrauma (11%). The prevalence of non-accidental trauma in pre-school children was high (44%). The mortality rate of non-accidental injuries is significantly higher compared to accidental injuries. The high incidence of neglect shows that awareness to this subject is needed to prevent future negligent injuries.